Merekabentuk dan Menilai Mesin Pelerai dan Penyisih Lada - Jusoh, Ahmad; Jaafar, Mohd Salih (Universiti Putra Malaysia Press, 1996)
Pepper (Piper nigrum L.) is an important cash crop in Malaysia, especially for the state of Sarawak. There are two major pepper products in international trade, white pepper and black pepper. This paper describes the performance of a mechanized pepper thresher and sorter which was designed and nibricated at Universiti Pertanian Malaysia. The machine serves three main functions: detaching berries from the stalks, separating detached berries from the empty stalks and separating large (> 5 mm diameter) and small berries for white and black pepper production, respectively. Tests were carried out to determine the optimum speed for threshing and sorting. The optimum operating speed for threshing was found to be 700 rpm. At this speed, the average threshing capacity was 338 kg/h with threshing efficiency of 99%; damaged berries accounted for less than 5%. The optimum operating speed for the sorting was found to be 280 rpm with the average sorting capacity of 415 kg/h.